Evidence of transmission of Mycobacterium tuberculosis by random amplified polymorphic DNA (RAPD) fingerprinting in Taipei City, Taiwan. - Harn, H J (1997)
AIMS: To determine, by strain identification of Mycobacterium tuberculosis, whether transmission has occurred between individuals or whether new strains are present. METHODS: A rapid protocol for random amplified polymorphic DNA (RAPD) analysis was developed. This protocol was applied to 64 strains of M tuberculosis that had been confirmed by culture and microbiological methods. RESULTS: There are five groups of M tuberculosis prevalent in Taipei city, Taiwan. The major types are groups I and III. Groups I and II had been prevalent until the end of last year when, according to our group analysis, they had been eradicated. However, group III was continuously present from the middle of 1995 to the middle of 1996, and group IV was present at the end of both years, which indicated that both groups were transmitted continuously. These clustered strains had demographic characteristics consistent with a finding of transmission tuberculosis. Also, there were 13 of 64 strains with unique RAPD fingerprints that were inferred to be due primarily to the reactivation of infection. In the drug resistance analysis, the major type represented included group III and part of group IV. CONCLUSIONS: Our preliminary data imply, not only that the prevalence of M tuberculosis in Taipei city is due to transmission rather than reactivation, but that drug resistance also may play a role in tuberculosis transmission.